2022
DOI: 10.1093/clinchem/hvac082
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Identification, Drug Susceptibility Test, and Whole-genome Sequencing of Helicobacter pylori Directly from Gastric Biopsy by Clinical Antimicrobial Susceptibility Test Ramanometry

Abstract: Background The battle against Helicobacter pylori (H. pylori) infections demands fast, reliable, and sensitive methods for pathogen identification (ID), antimicrobial susceptibility tests (ASTs) based on metabolic response, and genome-wide mutation profiling that reveals resistance mechanisms. Methods Here we introduce Clinical Antimicrobial Susceptibility Test Ramanometry for H. pylori (CAST-R-HP), and its validation with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…of 13.66% for 30-cell pools [63]). Together with our recent demonstration of deriving one-cell high-coverage genomes after RACS, such as 99.48% from urine [11], 99.70% from stomach [10] and 92.62% from soil [32], our findings further support the high genomic data quality and robustness of scRACS-Seq for various kinds of microbiome samples.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…of 13.66% for 30-cell pools [63]). Together with our recent demonstration of deriving one-cell high-coverage genomes after RACS, such as 99.48% from urine [11], 99.70% from stomach [10] and 92.62% from soil [32], our findings further support the high genomic data quality and robustness of scRACS-Seq for various kinds of microbiome samples.…”
Section: Discussionsupporting
confidence: 81%
“…1). (i) At the SCRS-based functional-cell detection step, a SCRS which is an intrinsic biochemical fingerprint of a cell can identify or classify the cell based on a wide range of metabolic functions [6][7][8] or via its taxonomy (e.g., for microalgae [9] or for bacteria [10]); in particular, the shifts of specific Raman bands in SCRS can quantitatively measure its substrate-intake activity, when substrates with stable isotopes (e.g. 13 C, 15 N, 2 H, 18 O) are assimilated by the cell [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Next, the transcriptome of E. coli persisters can be compared to those of the non-persister cells, on the basis of Raman-activated cell sorting and sequencing technologies (RACS-Seq) (He et al, 2019 ). We have recently demonstrated that such links of metabolic phenotype of targeting microbes and high-coverage genome sequences can be established at the resolution of the precisely single bacterial cell directly from human or soil microbiota (Xu et al, 2020 ; Jing et al, 2021 ; Liu et al, 2022 ), using Raman-activated gravity-driven single-cell encapsulation and sequencing (RAGE-Seq). Such efforts could promise to unveil the transcriptomic or epigenetic mechanisms that underpin microbial persistence in this model system.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of ramanome and MIC‐MA concepts, the (MP‐G) n data type, and the instrument series of CAST‐R, RACS‐seq, and FlowRACS, a comprehensive SCIVVS workflow to diagnose and treat infectious diseases has been demonstrated by clinical applications. For example, we established the CAST‐R‐HP approach that accomplishes single‐cell ID, AST, and high‐coverage whole‐genome sequencing of H. pylori directly from a gastric biopsy [38]. This approach consists of three steps: (a) treatment of clinical gastric biopsy specimens in medium with 50% D 2 O, 1% IsoVitale X™, Dent supplement, and a particular antibiotic, and then microaerobic incubation for 2–3 days for drug exposure without the need to isolate H. pylori ; (b) acquisition of SCRS for D 2 O‐treated, antibiotic‐challenged cells directly from the biopsy sample for rapid ID and AST of H. pylori single cells; (c) sorting of individual cells whose SCRS identifies H. pylori or the AST phenotype into microdroplets in a RAGE chip for a precisely one cell reaction of multiple displacement amplification and then shotgun sequencing, which produces a precisely one cell assembled genome with high coverage (>95%) to support genotype‐based validation of drug susceptibility, identification of new drug resistance mutations, and full genome‐based tracking of pathogens at one cell resolution [38].…”
Section: A Comprehensive and Integrated Instrument Solutions To Suppo...mentioning
confidence: 99%